LOBECTOMIA PULMONAR EM CANINO: RELATO DE CASO - de Cezaro, Tainara; Farret, Matheus Hilliard; Massa, Isadora Morais; Carneiro, Maico Fernando Wilges; Pinheiro, Fernanda (Anais de Medicina Veterinária; v. 2 n. 1 (2022): 2022/2, 2022)
.